Over expression of Her- 2 neu in ovarian surface epithelial carcinoma in a sample of Iraqi patient at Al-kindy Teaching Hospital. - AL-Kurtas, Mohammed , Abdul Mahdi (AL-Kindy College Medical Journal, 2013)
Background: Although expression of the HER- 2/neuoncogene may be of some prognostic importance in advanced ovarian cancer, its role in early-stage disease has not been established. The current study examined the prevalence and significance of HER- 2/neu expression in different grades of different types of surface epithelial ovarian carcinoma. Methods: Thirty eight female patients with surface epithelial ovarian cancer were included in this study. The blocks of corresponding formalin fixed, paraffinembedded ovarian biopsies were retrieved from the archives and hematoxylin-eosin slides of each ovarian biopsy were reviewed and marked their grades of differentiation , then a new sections from each sample stained by her2/neu as immunohistochemical technique and classified according to degree of intensity regarding to dependable scoring system , also ten cases taken as control group from normal ovarian tissue. Results :-Thirty eight sample of surface ovarian carcinoma were collected , twenty six were serous ovarian carcinoma , eleven cases were mucinous carcinoma type and one case was endometriod carcinoma . The samples were classified according to their histological types and according to their grading . The mean age of SC type was 54.52 with SD 7.17 while the mean age of mucinous carcinoma was 49.36 with SD 4.9. There is no significant relation between each type and grading system ( P Value = 0.9 ) ,also there is no significant relation between age group distribution and types of ovarian carcinoma ( P value = 0.14 ).Instate that statically no significant relation between intensity of expression Her2/neu and high grading of each types of collected sample ( P value =0.22) and this may be due to small sample size but still there are obvious criteria showing that her2/neu expression relatively increase in higher grade of each types of studied ovarian surface epithelial carcinoma. Conclusion :-In conclusion, the overexpression of the HER-2/neu gene product appears to be an unusual occurrence in early epithelial ovarian cancer and may occur less frequently than in advanced disease. Early ovarian cancer will eventually progress to advanced disease if undiagnosed and untreated, then, HER- 2/neu overexpression does not appear to be a general early event in the development of ovarian cancer. Instead, it seems that increased expression develops in many instances after the malignant phenotype has already arisen.